Expressive Speech Acts In Coco’s Movie By Darla K. Anderson - imron rosyadi; alfian alfian; adang ridwan (English Literature Department, Adab and Humanities Faculty, 2020)
The objective of this research is to describe the types of expressive speech acts, the use of expressive speech act, and the effects of expressive speech in Coco’s Movie by Darla K. Anderson. This research employs descriptive qualitative research. The object of this research isCoco’smovie by Darla K. Anderson. The data are classified from kinds of expressive speech acts by Austin’s theory. The use of expressive speech acts by using Yule’s theory. Then, the effect of expressive speech act were categorized by using Herbert. The findings of research show that there are six types of expressive speech acts, they are;expressive for thank 2 data, expressive for apologize 4 data, expressive for congratulation 2 data, expressive for greeting 2 data, expressive for wishes 2 data, and expressive for attitudes 2 data. Expressive for apologize was mostly dominant used by all characters. The use of expressive speech acts consist of direct and indirect, there were 5 data in direct and 3 data in indirect and direct was mostly dominant used by all characters. There were three effects of expressive speech acts, they were 3 data for getting knowledge, 2 data for giving command, and 2 data for asking for information. Moreover, the dominant effect of expressive speech is for getting knowledge in Coco’s movie.